Analisis Ketidaksantunan Berbahasa Netizen terhadap Kinerja Pemerintah dalam Penanganan Banjir Sumatera di Media Sosial X - Andika Kurniawan Luthfi; M. Daffa Amri; Muhammad Anis Rofiq; Nadif Abinaya Yulkham; Mikhail Aimran Sobirin; Asep Purwo Yudi Utomo; Sony Junaedi; Eko Ahmad Riyanto (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
The shift in communication patterns to digital public spaces, such as platform X, often triggers a disregard for language ethics, especially in crisis situations such as natural disasters. This phenomenon underscores the importance of examining how politeness is maintained or violated when people express their aspirations on social media. This study aims to identify and describe the forms of violations of the maxims of politeness committed by netizens regarding government policies in the context of disasters. The method used is descriptive qualitative with a listening and note-taking technique, referring to the theoretical framework of the ten maxims of politeness from Leech’s theory. The results of the study indicate a significant level of violation, with a dominance of the maxim of generosity using swear words, taboo words, and insults as a form of social protest and emotional expression. These verbal actions not only threaten the government's authority (face) but also indicate a degradation of language ethics in Indonesia's digital ecosystem. Theoretically, this study is useful for enriching pragmatic studies in digital linguistics. Practically, these findings provide a basis for evaluating how the public can convey public aspirations more effectively and constructively without harming the value of politeness in cyberspace.